Electronic Cigarette Awareness, Use, and Perceptions among Cancer Patients. Issue 2 (May 2018) - Buczek, Erin J.; Harrington, Kathleen F.; Hendricks, Peter S.; Schmalbach, Cecelia E.
Objective: Electronic cigarettes (e-cigs) are an emerging trend, yet little is known about their use in the cancer population. The objectives of this study were (1) to describe characteristics of e-cig use among cancer patients, (2) to define e-cig advertising exposure, and (3) to characterize perceptions of traditional cigarettes versus e-cigs. Study Design: Cross-sectional study. Setting: Comprehensive cancer center. Subjects and Methods: Inpatient, current smokers with a cancer diagnosis. E-cig exposure and use were defined using descriptive statistics. Wilcoxon rank test was used to compare perceptions between e-cigs and traditional cigarettes. Results: A total of 979 patients were enrolled in the study; 39 cancer patients were identified. Most cancer patients were women (59%), with an average age of 53.3 years. Of the patients, 46.2% reported e-cig use, most of which (88.9%) was "experimental or occasional." The primary reason for e-cig use was to aid smoking cessation (66.7%), alternative use in nonsmoking areas (22.2%), and "less risky" cigarette replacement (5.6%). The most common sources for e-cig information were TV (76.9%), stores (48.7%), friends (35.9%), family (30.8%), and newspapers or magazines (12.8%). Compared with cigarettes, e-cigs were viewed as posing a reduced health risk ( P < .001) and conferring a less negative social impression ( P < .001). They were also viewed as less likely to satisfy nicotine cravings ( P = .002), to relieve boredom ( P = .0005), to have a calming effect ( P < .001), and as tasting pleasant ( P = .006) Conclusions: E-cig use and advertising exposure are common among cancer patients. E-cig use is perceived as healthier and more socially acceptable but less likely to produce a number of desired consequences of cigarette use.